Deconstructing the Image of Third World Woman in Mohsin Hamid’s Exit West: A Postcolonial Feminist Perspective - Yasmeen, Tehmeena (Pakistan Languages and Humanities Review, 2022)
Pakistani writers, particularly Mohsin Hamid, have long highlighted women's struggle and their predicament under patriarchy in order to deconstruct their image as third-world women who remain passive against social and political injustices. Through the lens of postcolonial feminism as espoused in the classical postcolonial feminist works, “Three Women’s Texts and a Critique of Imperialism” and “Under Western Eyes: Feminist Scholarship and Colonial Discourses” written by Gayatri Chakravarty Spivak (1985) and Chandra Talpade Mohanty (1984) respectively, this study intends to explore how female characters in Hamid’s novel, Exit West question and deconstruct patriarchal and colonial values which subdued them in the name of societal or western enlightened norms. These articles are used to explain the novel in the context of postcolonialism in general and postcolonial feminism in particular to investigate gendered roles and women’s resistance to patriarchal forms of gender violence and oppression. The study's outcome revealed that colonialism and patriarchy impose gendered roles on women to deprive them of agency and problematise their identity formation processes and independent thinking.